ANALYSIS OF STEAM POWER PLANT RANKINE CYCLE EFFICIENCY ANALYSIS AT PT. PG RAJAWALI II JATITUJUH UNIT - Zauhari, Azi; Koswara, Engkos; Rachmat, Asep (Jurnal Mekanika dan Manufaktur, 2022)
Rankine cycle efficiency and rankine cycle work process at PT. PG Rajawali II Jati Tujuh Unit Adding knowledge to students about Rankine cycle in steam power generation system. To determine efficiency based on operational data. To know and understand the process of the Rankine cycle. It can be a reference and input for PT, PG Rajawali II Unit Jati Tujuh to see its efficiency. Before going into the field, we must prepare our theory according to the title such as boiler, turbine, condenser, pump example. This is a direct observation of the conditions at PT. PG Rajawali II Unit Jati Tujuh. This step is carried out to find out information about the conditions in the field and the situation where the practical work is carried out. Fractional pressure will not occur in the boiler and condenser, if the working fluid flows through the various components of a simple steam power cycle without irreversibility, and the working fluid will flow through the components at constant pressure. Dry water vapor from the boiler enters the turbine and undergoes a process isentropic expansion of the energy stored in the water vapor is converted into motion energy in the turbine. The water vapor is converted into liquid again so that it can be reused in the cycle process, PT. PG Rajawali II Unit Jati Tujuh on October 11, 2020 had the highest efficiency of 25.20%. October 22, 2020 has the lowest efficiency, which is 22.99%. Before going to the work process of the Rankine cycle, we must really understand the components related to the Rankine cycle, starting from the boiler, turbine, condenser, and pump so that we can understand and understand what the Rankine cycle is. In processing data using a help system, namely with Microsoft Excel with engineering applications, we have to ask those who know better so that in processing data with Microsoft Excel it can be actually clear in calculating it to get the values of pressure and temperature and their efficiency.